Borang soal selidik CC RAM28 (Bahasa Malaysia) - Mohamed Ludin, Salizar (2021)
The questionnaire was translated into Bahasa Malaysia and used as a tool in a study on the adaptation of the Australian Community Disaster Resilience scorecard & self-assessment of community disaster resilience (CDR): Kelantan's flood-affected communities